HE IMPORTANCE OF NEWBORN IDENTIFICATION TO THE DELIVERY OF SAFE PATIENT CARE - Adriana Pereira Trindade de Souza Gomes; Danielle Lemos Querido; Gloria Regina Gomes da Silva; Luana Ferreira de Almeida; Ronilson Gonçalves Rocha (Universidade Federal do Paraná, 2017)
A cross-sectional, observational and documentary study with a quantitative approach, performed at a Neonatal Unit of a University Hospital of Rio de Janeiro, from May to August 2016. Identification of neonatal patients through the use of bands was assessed. For this purpose, 200 observations were made. It was found that 155 (77.5%) newborn infants had identification bands. As for the place, 91 (58.7%) of the bands were around the ankles or wrists of the infants. Regarding the legibility of the information on the ID bands, this requirement was met in the ID bands of 76 (83.5%) newborn infants. In 46 (89.3%) observations, the ID band was not checked before the newborn was handed to a parent, nor was it checked prior to procedures in 45 (88.3%) of the cases. The patients' medical records included no information regarding identification bands in 174 (87%) cases, and its place in 179 (89.5%) of the cases. It was concluded that the referred neonatal unit failed to provide appropriate identification of the patients, and the implementation of strategies for improving safe care is urgently needed.